Ballistic - Greaney, Mark (Greaney, Mark. Gray Man novel., 2011)
"After he was betrayed by his compatriots and then forced to take on a near-suicidal covert mission by the CIA, master assassin Court Gentry thought he could find refuge off the grid, living in self-imposed isolation in the Amazonian rain forest. But even there, his bloody past finds him when a vengeful Russian crime lord forces him to go on the run once again. Without a country or a home to call his own, Court's options are narrow enough, but when he hears that an old friend has been murdered, he's compelled to pay his respects."--Page 4 of cover.